Triazatriangulenium salts - hosts and guests in supramolecular assemblies in solution - Sarkar, Sayan; Böck, Michael; Uhl, Agnes; Agafontsev, Aleksandr; Schatz, Jürgen; Kataev, Evgeny (Organic Chemistry Frontiers, 2024)
Self-assembly of triazatriangulenium dyes (TATA) bearing C3-C8 substituents and their interaction with aromatic compounds were studied. The dyes with alkyl chains longer than C5 were strongly aggregated in solution, while those with shorter alkyl chains formed hetero-stacks with aromatic compounds in chloroform. Anthracene, pyrene, coronene, and a naphthalene diimide dye formed heterostacks in solution with association constants 104 M−1. Anthracene and pyrene-based water-soluble cyclophanes were designed to investigate host-guest complexes with TATA dyes in an aqueous solution. Experimental and theoretical investigations suggest that only pyrene-based cyclophane is able to encapsulate TATA dyes. These self-assembled structures constitute new supramolecular motifs to construct multilayered organic structures.
CRIS-Team Scopus Importer:2024-04-26